Manejo da irrigação: uso da termometria por infravermelho para a detecção de estresse hídrico na cultura da soja - Moura, Murilo Brum de (2022)
Soybean cultivation has expanded in recent years, both in Brazil and in other countries. However, what most limits productivity is the water deficit, which can be overcome by using supplementary irrigation. Therefore, an accurate water requirement estimate is necessary to ensure efficient irrigation management. In this way, irrigation management can be based on soil, atmosphere, and plant, and from a physiological point of view, plant-based irrigation is one of the most accurate. From it, the Crop Water Stress Index (CWSI) was calculated. Therefore, this work aims to measure the canopy temperature during soybean crop season to quantify the water stress index of the crop through the empirical methodology proposed by Idso et al. (1981) and the analytical methods of Jackson et al. (1981). For this, infrared thermometers (TIV) were installed above the canopy to monitor the crop from full ground cover by the canopy to the end of the cycle. The cultures were submitted to different levels of water stress. The canopy temperature data for calculating the water stress index were associated with other meteorological parameters, such as net radiation, wind speed, air temperature, and relative humidity. One of the first responses of plants to water deficit is stomatal closure and consequent reduction in transpiration. Since transpiration requires energy, the leaves absorb the energy that would be dissipated and heated up when water is lacking for the process to occur. So, plants in optimal water status had lower canopy temperatures, indicating a relationship between water status and plant temperature canopy. Comparing the two methodologies, it was observed that there is a good correlation between them. However, the empirical method presented more significant variation between the results, being an easy-to-use approach.